2004
DOI: 10.1371/journal.pbio.0020007
|View full text |Cite
|
Sign up to set email alerts
|

Gene Expression Signature of Fibroblast Serum Response Predicts Human Cancer Progression: Similarities between Tumors and Wounds

Abstract: Cancer invasion and metastasis have been likened to wound healing gone awry. Despite parallels in cellular behavior between cancer progression and wound healing, the molecular relationships between these two processes and their prognostic implications are unclear. In this study, based on gene expression profiles of fibroblasts from ten anatomic sites, we identify a stereotyped gene expression program in response to serum exposure that appears to reflect the multifaceted role of fibroblasts in wound healing. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

29
804
0
11

Year Published

2006
2006
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 852 publications
(846 citation statements)
references
References 46 publications
29
804
0
11
Order By: Relevance
“…From the microarray data, we found that several genes in the RAS and PI-3 kinase pathways were transcriptionally affected by serum stimulation, as has also been shown for wild-type human and wild-type mouse fibroblasts that were serum stimulated from G 1 (Iyer et al, 1999;Chang et al, 2004). However, serum stimulation does not only result in a transcriptional response, but also in activation of the RAS and PI-3 kinase pathways through post-translational modifications, such as phosphorylation (Campbell et al, 1998).…”
Section: Cell-cycle Re-entry Of G 2 -Arrested Cells Depends On Ras Ansupporting
confidence: 64%
See 1 more Smart Citation
“…From the microarray data, we found that several genes in the RAS and PI-3 kinase pathways were transcriptionally affected by serum stimulation, as has also been shown for wild-type human and wild-type mouse fibroblasts that were serum stimulated from G 1 (Iyer et al, 1999;Chang et al, 2004). However, serum stimulation does not only result in a transcriptional response, but also in activation of the RAS and PI-3 kinase pathways through post-translational modifications, such as phosphorylation (Campbell et al, 1998).…”
Section: Cell-cycle Re-entry Of G 2 -Arrested Cells Depends On Ras Ansupporting
confidence: 64%
“…This indicates that the microarray data of the serum-stimulated TKO-BCL2 MEFs were of sufficient quality for further analyses. Oncogenic pathways impinging on the G 2 -restriction point F Foijer et al et al, 1999;Chang et al, 2004). To understand which processes were occurring in cells released from G 2 arrest, we have used Genesis to group genes in 10 different clusters using k-means clustering, each showing a specific expression profile over time.…”
Section: Resultsmentioning
confidence: 99%
“…On the basis of the gene expression profiles of fibroblasts from 10 anatomic sites, Chang et al, 29 were recently able to identify a stereotyped gene expression program in response to serum exposure that seems to reflect the multifaceted role of fibroblasts in wound healing. Recently, it has been shown that genes induced in the fibroblast serumresponse program are expressed in tumors by the tumor cells themselves, by tumor-associated fibroblasts, or both.…”
Section: Macro-environment Of Breast Carcinoma F Moinfar Et Almentioning
confidence: 99%
“…Moreover, the molecular features that define this wound-like phenotype are evident at an early cancer and predict increased likelihood of metastasis and death in breast, lung, and gastric cancer. 29 In a subsequent study of 295 early breast carcinomas, Chang et al 30 showed that both overall survival and distant metastasis-free survival are significantly diminished in patients whose carcinomas expressed this 'wound-response signature' compared to tumors that did not express this signature. 30 At this point, it is not clear whether the observed genetic changes in our current study are related to breast cancer initiation or are acquired 'reactive' genetic alterations which are more associated with tumor progression.…”
Section: Macro-environment Of Breast Carcinoma F Moinfar Et Almentioning
confidence: 99%
“…Cancer cells do not invent new pathways, but resurrect the pre-existing but dormant signaling pathways that were active during embryonic development or normal physiological condition. In recent studies (Chang et al, 2004(Chang et al, , 2005, gene expression signatures from experimental condition mimicking wound healing process were used to measure how much tumors may be like wounds, and developed a model to predict cancer progression based on wound healing gene expression signature. Patients carrying the wound healing signature had a significantly increased risk of metastasis when compared with patients who lack the signature, indicating that genomic data from normal physiological condition can help to predict the prognosis of cancer patients.…”
Section: Integrative Functional Genomicsmentioning
confidence: 99%